ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN TAHAPAN KASTOLAN DI KELAS VIII SMP NEGERI 7 PADANG - Suhada Ramzah, Winny Fajarny (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematics is an important subject at every level of education. The problem that needs attention in the field of mathematics is the number of errors made by students in solving math problems. The purpose of this study is to examine and describe the factors that contribute to the category of student errors that occur in class VIII SMP Negeri 7 Padang in solving math problems, according to the Kastolan stages. The errors investigated are based on the error categories in the Kastolan stages which include technical errors, procedural errors, and conceptual errors. The research method used was descriptive research, with the research subjects as many as 20 students of class VIII.4 SMP Negeri 7 Padang. Interview guideline documents and test questions with statistics material were used as research instruments. The results of the study showed that (1) the number of students who made conceptual errors was 45.58% because students did not understand the concept of the material/meaning of the problem and were unable to determine the correct formula. (2) there were 29.30% of students who made procedural errors caused by a lack of understanding of the material so that they had difficulty in making steps to solve it. (3) As many as 25.12% of students made technical errors because students were still slow in carrying out arithmetic operations, careless/not careful in completing questions so that writing errors and errors in arithmetic operations often occurred.Keywords – Analysis of Student Errors, Errors According to Kastolan Stages, Conceptual Errors, Procedural Errors, Technical Errors